The XXI Century Bureaucrat: From Rational Dictatorship to Optimal Management Democratization (Palimpsesto, 2022)
There has been a debate that has generated controversies among professional circles, which lies in the confrontation of the sacrosanct dogma of the efficiency and effectiveness of public administration and the participation of people in the decisions of public management, including the lack of political participation in this area, against the notion of a State open to citizens, considering the risks in the feasibility of the work itself. It is in this scenario that the civil servant of this century considers the need to reconcile both perspectives, in pursuit of the development of modern public management, which will be analyzed from a perspective of historical evolution and impact on the management of state institutions.
Keywords: Rationality; Democracy; Participation; Bureaucrat; Citizenship